Phosphodiester Conjugation of Metronidazole and Dexamethasone as Possible Mutual Prodrug - Muthana D. Saud; Suhair M. Ghani (College of Pharmacy University of Baghdad, 2017)
As possible mutual prodrug had been synthesized that contain metronidazole and dexamethazone conjugated through phosphodiester linkage. The rationale for this type of conjugate is to get a prodrug with possible site â€" specific delivery of its active constituents into the lower parts of the G.I.T. This compound was synthesized by the reaction of dexamethzone â€" 21 â€" phosphate with metronidazole to form:(1 â€" (dexamethazone â€" 21 â€" phosphoryl) â€" metronidazole)    This conjugate was performed using dicyclohexylcarbodiimide (DCC) as a condensing agent. The identity of the prepared compound had been confirmed using T.L.C., U.V. spectroscopy, IR spectroscopy and elemental analysis. The partition coefficient for it had also been determined through n â€" Octanol / water partitioning system.